Study of Molecular Interactions, Optical, and Structural Properties through the Green Synthesis of Selenium Oxide Nanoparticles from Hibiscus sabdarriffal: Biocompatibility for Biophysics - Ali Bahari; Saad I. Esmail; Ashraf M. Alattar (Journal of Medical Physics)
Background: Recently, the green synthesis process has been utilized to manufacture a large quantity of metal nanocrystallites due to its low cost and the availability of numerous natural resources and the find the activity of bacteria and viruses that in the body of humans. Aims and Objectives: In this study, nanocrystallites of selenium oxide were produced utilizing Hibiscus sabdariffa. Researchers have analyzed the antibacterial properties and nanostructure characteristics of selenium oxide nanocrystallites using various techniques methods, such as imaging microscopy, scanning electron microscopy, ultraviolet‒visible spectroscopy (UV‒VIS), transmission electron microscopy, atomic force microscopy, and X-ray diffraction (XRD) spectroscopy. Results: According to the results, the films are discovered to have a nanocrystalline structure in a cubic spinel configuration. The crystallites are semispherical in shape and are both uniform and easily distributed. The XRD data were recorded on card number 22-1314, and the 2 θ (hkl) value was 38.351 (311). The UV‒VIS spectrum of the material exhibited a plasmon resonance peak at 272 nm, confirming the presence here of selenium oxide. This study also investigated the response of four distinct strains of pathogenic bacteria to biosynthesized selenium oxide nanoparticles (NPs). The data indicate that the biosynthesized selenium oxide NPs were highly effective against Klebsiella spp. and had the lowest effectiveness against Staphylococcus aureus, Staphylococcus epidermidis, and Escherichia coli. Conclusions: The utilization of selenium oxide nanocrystals as antibacterial agents has yielded diverse outcomes, demonstrating their remarkable efficacy in combatting Klebsiella spp.